PREPARING FUTURE PRIMARY SCHOOL TEACHERS FOR ENVIRONMENTAL EDUCATION OF YOUNGER STUDENTS - SHEVCHUK, Krystyna (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2025)
Environmental protection is a global issue of our time, directly affecting the survival of humanity. The intensification of the environmental threat on a global scale has made the issues of environmental education for schoolchildren particularly urgent. This article summarises that the development of environmental culture among schoolchildren is built on integrating three interrelated processes – environmental education, environmental upbringing, and environmental enlightenment. Environmental education is an integral part of general education, aimed at forming students' system of ecological knowledge, skills, and competences, reflecting the relationship between humans, nature, and society. Environmental enlightenment involves spreading ecological knowledge and promoting information about nature conservation and the rational use of natural resources. Environmental upbringing is focused on developing spiritual qualities that foster a responsible and caring attitude towards nature. Environmental education, upbringing, and enlightenment are directed towards harmonising human-environment relations and addressing numerous environmental issues. Therefore, it is essential to prepare teachers methodologically for implementing environmental education. The methodological basis for preparing future teachers for the environmental education of primary school students includes traditional ethical principles, global principles of sustainable development, and professional ethics principles for teachers. It is generalised that environmental education and enlightenment of future primary school teachers play a crucial role in their ecological training, as the effective assimilation of ecological knowledge and values by schoolchildren occurs at the primary school age, a time characterised by emotional sensitivity, vulnerability, curiosity, and high motivation for learning and engaging in various socially beneficial (including environmental) activities, given their age and psychological traits. The goal of ecological training for students in pedagogical fields is defined as the formation of eco-pedagogical literacy, equipping future primary school teachers with basic ecological knowledge, ethical-ecological values, pedagogical attitudes, environmental behaviour skills, and methods for ensuring the environmental focus of the educational process, which collectively contribute to preparing future teachers for environmental education of young pupils.